PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) BERBANTUAN MEDIA VIDEO ANIMASI TERHADAP KETERAMPILAN MENULIS TEKS PUISI SISWA KELAS IV SDN 34 AIR PACAH PADANG - Dea, Dea Nabila; Azkiya, Hidayati; Syofiani, Syofiani; Rinaldi, Rio (JIPD (Jurnal Inovasi Pendidikan Dasar), 2024)
This study was initiated due to the observed low writing skills among fourth-grade students at SDN 34 Air Pacah Padang. It encompassed the entire fourth-grade student body of SD Negeri 34 Air Pacah Padang, which is divided into two classes, IV A and IV B, totaling 52 students—26 in each class. The research sample designated class IV A as the experimental group and class IV B as the control group. A non-probability sampling method, specifically saturated sampling, was utilized for sample selection. This research adopted a quantitative approach through a true experimental design. Data collection was conducted through performance tests to assess the poetry writing skills of students in both class IV A and IV B of SD Negeri 34 Air Pacah Padang. The data analysis involved normality and homogeneity tests. The findings indicated that the conventional teaching model employed in class IV B resulted in poetry writing skills below the established KKTP standard of 70, with a score of 68.59. Conversely, the application of a project-based learning (PjBL) model, augmented by animated video media, significantly improved the writing skills of class IV A students, achieving a score of 78.37, thereby meeting the predefined KKTP standard. The study concludes that the project-based learning model, supported by animated video media, substantially enhances the poetry writing skills of fourth-grade students at SDN 34 Air Pacah Padang.